Effect of Packaging and Storage Conditions on Stability of Perindopril Tablets - Pehlivanović, B.; Ridžanović, E.; Ćatović, E.; Pašić-Kulenović, M. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Stability of a pharmaceutical product may be defined as the capability of a particular formulation in a specific container to remain within its physical, chemical, microbiological and toxicological specifications. Perindopril is a nonsulfhydryl prodrug belonging to the angiotensin-converting enzyme (ACE) inhibitor class of medications, used to treat essential hypertension, congestive heart failure and to reduce cardiovascular risk. The aim of this study was to evaluate stability and quality of Perindopril tablets (2 mg, 4 mg and 8 mg) over time. Tablets were packed in PVC/PVdC/Al blisters and Al/Al blisters and stored at accelerated (40°C/75%RH) and long-term (25°C/60%RH) conditions. Physical and chemical stability was measured after 3 and 6 months. HPLC analysis was used for determination of assay, related substances, dissolution and water content. The results show significant decrease of assay for Perindopril tablets packed in PVC/PVdC/Al blisters, while Al/Al blisters maintained better pharmaceutical performance.